(untitled) (World Bulletin of Social Sciences, 2024)
This article is devoted to the identification of rapidly effective strategies for the use of modern technologies in teaching English, as well as the study of methods for improving the professional skills of veterinary students on the basis of English. The article currently addresses issues related to the level to which the teacher can Interest students in the lesson and get them knowledge in order to use pedtechnologies in teaching English to students of Veterinary Specialty in the educational process and for the lessons to give an effective result